Analysis of the Young Generation’s Understanding of Pancasila as the Ethics of National and State Life - Weffani, Anggi; Waspiah, Waspiah (Journal of Creativity Student, 2021)
Every nation has ethics and norms in carrying out its activities. The ethics of national life is formulated with the aim of becoming a basic reference for improving the quality of human beings who are faithful, pious and have noble character and have Indonesian personalities in the life of the nation. However, how far has the understanding of the younger generation in understanding the ethics of national and state life gone? Pancasila must be maintained by all Indonesians as the basis of the state and ideology because Pancasila is the life that has been embedded since the birth of the Indonesian nation and state. To foster the value of Pancasila awareness among the younger generation, these are as follows: (1) Pancasila as a view of life and the basis of the state, (2) the ability of the younger generation to adapt to the world, (3) the young generation is able to regulate and maintain and cultivate the value of Pancasila awareness, and (4) the younger generation has a common goal to transform with the community and its leaders.